2014
DOI: 10.1200/jco.2014.32.3_suppl.305
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of FOLFIRINOX in patients with metastatic pancreatic cancer.

Abstract: 305 Background: FOLFIRINOX, one of the gold standard in metastatic pancreatic cancer as first-line therapy for patients under 76 years with PS 0-1, good haematological and renal function and a subnormal bilirubin level (Prodige 4 criteria), was analysed in Brittany (B) and Pays de la Loire (PL) in routine clinical practice. Methods: Our aim is to evaluate the use of Folfirinox between July 2010 and December 2012 in B/PL. Results: Data of 340 patients have been studied (198 men, median age 63 years [29-81]). 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, it cannot be applied to all patients with pancreatic cancer due to severe toxicity of the FOLFIRINOX, such as neutropenia, leucopenia, febrile neutropenia, anorexia, and diarrhea. The study by Metges et al who are the original investigators in the PRODIGE 4/ACCORD 11 trial, based on their established criteria, showed that 81% of 242 patients required a dose reduction (median dose intensity; 5-FU bolus 82%, oxaliplatin 78%, irinotecan 81%), but that this result did not affect treatment efficacy compared to the PRODIGE 4/ACCORD 11 trial: RR 39% vs. 32%, median PFS 6.5 vs. 6.4 months, and median OS 10.9 vs. 11.1 months [ 10 ]. A Japanese phase II trial of the FOLFIRINOX showed that grade 3 or 4 neutropenia and febrile neutropenia were more frequently observed compared to those in the global phase III trial (77.8% vs. 45.7%, 22.2% vs. 5.4%, respectively) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it cannot be applied to all patients with pancreatic cancer due to severe toxicity of the FOLFIRINOX, such as neutropenia, leucopenia, febrile neutropenia, anorexia, and diarrhea. The study by Metges et al who are the original investigators in the PRODIGE 4/ACCORD 11 trial, based on their established criteria, showed that 81% of 242 patients required a dose reduction (median dose intensity; 5-FU bolus 82%, oxaliplatin 78%, irinotecan 81%), but that this result did not affect treatment efficacy compared to the PRODIGE 4/ACCORD 11 trial: RR 39% vs. 32%, median PFS 6.5 vs. 6.4 months, and median OS 10.9 vs. 11.1 months [ 10 ]. A Japanese phase II trial of the FOLFIRINOX showed that grade 3 or 4 neutropenia and febrile neutropenia were more frequently observed compared to those in the global phase III trial (77.8% vs. 45.7%, 22.2% vs. 5.4%, respectively) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Grade 3/4 toxicities were reported in 10 patients: nausea/vomiting in one, diarrhea in one, fatigue in three, neutropenia in four, thrombocytopenia in one, and febrile neutropenia in three—all manageable. A follow-up study by the original investigators in the PRODIGE 4/ACCORD 11 study, based on their established criteria, showed that 81% of 242 patients required a dose reduction, but that this did not affect results (response rate 39% vs. 32%, PFS 6.5 vs. 6.4 months and OS 10.9 vs. 11.1 months) 27 .…”
Section: Do Modifications To the Ffx Regimen Matter?mentioning
confidence: 99%
“…In spite of such intensity of treatment and much larger toxicity in grade 3 and 4, no deterioration of quality of life was observed among the patients treated with FFX [13]. Irrespective of the initial doubts related to the large toxicity of FFX, this regimen was quickly introduced into clinical practice and until today it has been undergoing numerous modifications -these are mFOLFIRINOX (mFFX) which reflect the attempts to reduce toxicity accompanied with the preservation of the treatment efficacy [14][15][16][17][18][19].…”
Section: Practical Clinical Division Into Sub-groupsmentioning
confidence: 99%